Zarys struktur oraz zadania Zwiadu Wojsk Ochrony Pogranicza i Kontroli Ruchu Granicznego w latach 1945–1991 - Grabowski, Łukasz; Maruszak, Marcin (Pamięć i Sprawiedliwość, 2012)
This article presents an outline of the structures, organisational hierarchy and tasks of the Reconnaissance of the Border Defence Army (Wojsko Ochrony Pogranicza) and the Border Traffic Control (Kontrola Ruchu Granicznego) units that were subordinate to WOP and the Ministry of Interior in the years 1945–1991. The main tasks of the abovementioned bodies that constituted part of the quite vast repression apparatus of the communist state consisted in the operational securing of borders and border traffic, as well as counteracting all activities threatening safety and security, and the political system of the state in the border zone. The organisation was established on 27 September 1945 under the order of the Supreme Commander of the Polish Armed Forces. In the first period of its existence, it was subordinate to the Ministry of National Defence. In 1949, it became part of the Main Inspectorate for Border Protection and, as a result, it was subordinate to the Ministry of Public Security (MBP). Intelligence departments based at the headquarters and their counterparts at the level of brigades and battalions were responsible for operational activities. In 1965, the General Headquarters of WOP, together with their subordinate units, became part of the newly-established Ministry of Interior, and since 1961, Command II (Reconnaissance) of the WOP General Headquarters and its subordinate units, as well as KRG bodies, became subordinate to Department II of the Ministry of Interior in the scope of operational activities. However, already in 1965, the WOP General Headquarters and its subordinate field units were excluded from the Ministry of Interior and, in organisational terms, became subordinate to the Main Inspectorate of Territorial Defence of the Ministry of National Defence. The previous KRG Units remained part of the Ministry of Interior. They were incorporated into the KRG MI Command that functioned as part of the SB division in July 1965. In October 1965, on the basis of the previous WOP General Headquarters, the Head of WOP was established. At the newly-formed body, intelligence activities were the responsibility of the Command of Reconnais-sance of the Head of WOP and its subordinate units. In 1979, the Head of WOP was excluded from the Ministry of National Defence and was made subordinate to the Ministry of the Interior once again in the scope of command. It assumed the name of “WOP Command”. At the time, the Command of Reconnaissance of the Head of WOP was composed of KRG organisational units that were then excluded from the Ministry of Interior. As a result, a uniform system of border protection was restored within the Ministry of Interior. The fact that General Czesław Kiszczak assumed the function of Minister of Interior in July 1981, as well as the further consequences of martial law introduction, resulted in tightening cooperation between WOP and MO and SB bodies, as well as in expanding the scope of the tasks of the Command of Reconnaissance of the Head of WOP.The basic changes included the take-over of some border-related tasks of the SB by the WOP Reconnaissance, especially: protection of border customs offices and their agendas, borderline railway stations and ports, prevention, identification and detection of all hostile criminal activity and illegal and anti-state organisations in the border zone.